HUBUNGAN PERHATIAN ORANG TUA DAN CARA BELAJAR DENGAN PRESTASI BELAJAR AKUNTANSI SISWA KELAS X JURUSAN AKUNTANSI SMK MUHAMMADIYAH 2 BANDAR LAMPUNG - Zainal, Vetri Yanti (LPPM STKIP PGRI Bandar Lampung, 2016)
The study aims to determine the relationship between parental attention and learning styles to the students’ learning achievement of Accounting of SMK Muhammadiyah 2 Bandar Lampung. This study uses correlation survey method. The population in this study were all students of class X in Accounting totaling 45 students. The sample used in this study came from all population.Research results revealed that (1) there is a positive and significant relationship between parental attention and learning achievement of Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung. (2) there is a positive and significant relationship between learning style and academic achievement of Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung. (3) there is a positive and significant correlation between parental attention, learning style and the learning achievement of class X Accounting class at the tenth grade students of SMK Muhammadiyah 2 Bandar Lampung.